2012
DOI: 10.5933/jkapd.2012.39.3.233
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photodynamic Therapy on the Viability of Streptococcus Mutans Isolated From Oral Cavity

Abstract: Photodynamic therapy (PDT) is a technique that involves the activation of photosensitizer by light in the presence of tissue oxygen, resulting in the production of reactive radicals capable of inducing cell death. The aim of this study was to evaluate the effect of PDT on Streptococcus mutans in planktonic conditions, previously treated with different photosensitive concentrations of erythrosine, using halogen and LED curing unit as a light source. And we compared the effects of PDT on six strains of S. mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
6
0
1
Order By: Relevance
“…The CFU counts immediately after treatment were significantly lower in Group II (PDT) than in Group I (negative control), thus verifying the antimicrobial ability of erythrosinemediated PDT on S. mutans. This is consistent with the results of previous studies [9,[11][12][13][14][15]. The American Society of Microbiology defines antimicrobial activity as a ≥3 log CFU/mL reduction from the starting inoculum [16].…”
Section: ⅳ Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The CFU counts immediately after treatment were significantly lower in Group II (PDT) than in Group I (negative control), thus verifying the antimicrobial ability of erythrosinemediated PDT on S. mutans. This is consistent with the results of previous studies [9,[11][12][13][14][15]. The American Society of Microbiology defines antimicrobial activity as a ≥3 log CFU/mL reduction from the starting inoculum [16].…”
Section: ⅳ Discussionsupporting
confidence: 91%
“…Studies have reported the use of erythrosine as a photosensitizer in PDT to exert antimicrobial effects against S. mutans cells in suspensions or biofilms [9,[11][12][13][14][15]. After antimicrobial treatment, residual bacteria induce the recovery of biofilm growth and CFU counts, indicating the possibility of reinfection.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, disadvantages of a halogen curing unit is the de- been widely used [25]. A study on PDT using halogen as a light source and erythrosine as a photosensitizer for planktonic S. mutans reported an effective reduction in viability [26].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Due to the differences in the amount of energy irradiated, the LEDs failed to show the results of effective photodynamic therapy [24]. Others conducted a study on PDT using 600 mW/cm 2 of halogen and 900 mW/cm 2 of LED, and irradiated 18 J/cm 2 and 27 J/cm 2 respectively [26]. Both light sources were effective.…”
Section: ⅳ Discussionmentioning
confidence: 99%